Analysis Of The Use Of Oral Antidiabetic Drugs In Type II Diabetes Mellitus Patients At X Hospital Semarang City - Wibowo S, F.X. Sulistiyanto; A., Dhimas; C.S., Insania (Dian Nuswantoro Semarang, 2025)
Diabetes mellitus is a long-term condition marked by high blood sugar levels. It stems from metabolic endocrine disorders that may result from reduced insulin secretion, reduced insulin sensitivity, or both. Management of type II DM often includes antidiabetic treatment, which may consist of one medication or a combination. This research aims to describe patient characteristics, outline medication usage, report rates of Glucose Ad Random (GAR) reduction, and assess the efficacy of single versus combination antidiabetic drugs in type 2 DM patients admitted to X Hospital in Semarang City. The study uses an analytical observational approach with retrospective data collection and purposive sampling. Findings showed that 52.13% were women and 42.02% were aged 56-65 years (late elderly group). Also, 70.21% had Type II DM with complications, and 57.45% had hospital stays of 1-4 days. The most used single antidiabetic accounted for 53.19% of cases. Paired Sample T-Test results for both single and combination antidiabetics showed p <0.05, indicating both therapies effectively reduce GAR. Single antidiabetic therapy yielded a 22.46% reduction, while the combination led to a 45.36% decrease. The T-Test results further showed the combination was more effective, with an average GAR reduction of 111.2386 mg/dL. Hospitals are expected to continue using combination oral antidiabetics as per the hospital formulary to maintain blood sugar control. Diabetes Mellitus patients should monitor blood sugar routinely, take medications regularly, and follow a recommended diet, healthy lifestyle, and regular exercise. This helps prevent complications. Future researchers are encouraged to examine the relationship between laboratory data and other factors such as BMI, diet, and stress.